Characteristics of meaningful activities in community-dwelling Japanese older adults with pre-frailty and frailty. (March 2022) - Maruta, Michio; Makizako, Hyuma; Ikeda, Yuriko; Han, Gwanghee; Shimokihara, Suguru; Miyata, Hironori; Nakamura, Atsushi; Tokuda, Keiichiro; Kubozono, Takuro; Ohishi, Mitsuru; Tomori, Kounosuke; Akaida, Shoma; et al.
Highlights: This study investigated the association between frailty and meaningful activity. Meaningful activities may be affected by frailty and cognitive impairment. Activity satisfaction was unaffected by frailty and cognitive impairment. Activity performance was unaffected by frailty and cognitive impairment. Careful assessment of meaningful activities in frail older adults is important. Abstract: Objectives: This cross-sectional study aimed to clarify the association between physical and social frailty, cognitive impairment, and meaningful activity in older adults. Methods: Data were obtained from 747 older adults (mean age, 74.7 ± 6.2 years; women, 63.9%) who participated in a community-based health check survey (Tarumizu Study 2018). Physical frailty, cognitive impairment, and social frailty were evaluated using the Fried phenotype model (exhibiting one or more of the criteria, including having a pre-frailty status); computerized cognitive test including memory, attention, executive functions, and processing speed (having a score below an age-education adjusted reference threshold in one or more domains); and Makizako's 5 items (exhibiting one or more of the criteria, including having a pre-frailty status), respectively. Participants selected meaningful activities from the 95 activities included in the Aid for Decision-Making in Occupation Choice, after which their satisfaction and performance were evaluated. Meaningful activities were categorized into physical activity, cognitive activity, social activity, and other daily activity. Results: The physical frailty group was significantly less likely to choose physical activity over other activities ( p < 0.05). The cognitive impairment group was significantly less likely to choose cognitive activity over other activities ( p < 0.01). The multi-domain frailty group (including cognitive impairment) was significantly less likely to choose social activity over other activities ( p < 0.05). No significant differences in satisfaction and performance were observed according to frailty status. Conclusions: Our findings indicated that physical and social frailty and cognitive impairment may affect participation in meaningful activities corresponding to these domains.